The comparative functional anatomy of the forelimb in two african mole-rat species, bathyergus suillus and heterocephalus glaber - Doubell, Narusa Suria (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc)--Stellenbosch University, 2021.